Knowledge management through competencies: an exploratory study in the automotive industry sector - Martins, Dora (2021)
Organisations and human resources managers (HRm) are currently facing a new set of obstacles and experiencing an urgent need to keep up with the expanding digitalization brought by the Digital Age. This has caused a great impact on business success and sustainabilíty and as well as concerns regarding much-needed refreshed competencies for effective performance. Despite the global influence caused by this scenario, the industry is one of the most affected sectors, particularly in the automotive area. This study focuses on understanding HRm's opinions and beliefs including competency shifts caused by the influences and obstacles of the digital era in the automotive industry sector. The investigation carried out, assumed a qualitative methodology by applying eleven semi-structured interviews that collected the participants' perspectives and their concerns regarding the influences and challenges brought by the digital age including its impact on the change of competencies sought by organisations. AII participants were active human resources (HR) professionals in different organisations in the automotive industry sector. The results showed that new topics such as competitiveness and continuous improvement gained substantial importance and that new challenges surfaced with the evolution of technology, such as employee's difficulty to adapt and the impact of technology on their socialization levels. In contrast, the shortening of physical distances through technology was seen as the major advantage. Additionally, this study points to digital competencies, technical capacity, Microsoft Office proficiency, proactivity, and cooperation as the current most valued competencies for automotive industry sector organisations. Further discussion was taken into consideration regarding the study results obtained confirming the impact of technology in the competencies profiles of automotive industry sector organisations. It can be concluded that the study's contributions and shortcomings are highlighted in addition to further suggestions made regarding future research on the theme.